Histopathological changes in naive and sensitised goats caused by Sarcoptes scabiei infestation - Tarigan, Simson (Indonesian Journal of Animal and Veterinary Sciences, 2003)
The purpose of this study is to compare the histopathological changes in naÃ¯ve and sensitised goats caused by Sarcoptes scabiei infestation. Thirty goats were allocated evenly into 5 groups. Groups 1, 2 and 3 goats were sensitised once, twice and thrice, respectively; whereas groups 4 and 5 were left unsensitised or naÃ¯ve. Sensitisation was done by infesting the animals with the mite, then 7 week afterwards the animals were completely cured from the mange. After the sensitisation, all, except group 5, goats were infested on both auricles each with approximately 2000 life mites. Biopsies were collected from each group at 2 day then at weekly intervals from 1 to 7 weeks following infestation. The samples were routinely processed, paraffin blocked, and tissue sections were stained with Haematoxyllin and Eosin (H & E), Giemsa, Carbol Chromatrope, and Gramâs when indicated. Lesions in the naÃ¯ve goats developed progressively characterised by thick parakeratotic crusts honeycombed with tunnels containing large number of mites. Lesions in sensitised goats, which were different qualitatively to those in naÃ¯ve goats, developed rapidly characterised by copious amount of serocellular exudates in and on the surface of the epidermis, and marked oedema and cell infiltrations in the dermis. Dermal infiltration by eosinophils, which was rare in naÃ¯ve goats, was apparently an important feature in the sensitised goats. Lesions developed in the sensitised goats were interpreted to be the manifestation of cutaneous anaphylaxis. Resistance or protective immunity against mite reinfestation developed in the sensitised goats is supposedly attributed to this anaphylactic responses. Â  Key words: Sarcoptes scabiei, naÃ¯ve, sensitised, histopathology, eosinophils, cutaneous anaphylaxis, protective immunity